2012
DOI: 10.1094/mpmi-06-11-0166
|View full text |Cite
|
Sign up to set email alerts
|

Ralstonia solanacearum Needs Flp Pili for Virulence on Potato

Abstract: Type IV pili are virulence factors in various bacteria. Several subclasses of type IV pili have been described according to the characteristics of the structural prepilin subunit. Although type IVa pili have been implicated in the virulence of Ralstonia solanacearum, type IVb pili have not previously been described in this plant pathogen. Here, we report the characterization of two distinct tad loci in the R. solanacearum genome. The tad genes encode functions necessary for biogenesis of the Flp subfamily of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 69 publications
4
35
0
1
Order By: Relevance
“…The strongest effects were observed in BGPG2, with this gene cluster being downregulated more than 10-fold compared to the levels of expression in the wild-type strain (see Table S1 in the supplemental material). We can only speculate that the B. glumae Flp pilus plays a crucial role during the infection process, as recently shown for the plant pathogen Ralstonia solanacearum (73). It is likely that the downregulation of Flp pilus genes is also responsible in part for the motility phenotypes observed in Fig.…”
Section: Global Pattern Of Qs-dependent Gene Expression In Bgpg1supporting
confidence: 61%
See 1 more Smart Citation
“…The strongest effects were observed in BGPG2, with this gene cluster being downregulated more than 10-fold compared to the levels of expression in the wild-type strain (see Table S1 in the supplemental material). We can only speculate that the B. glumae Flp pilus plays a crucial role during the infection process, as recently shown for the plant pathogen Ralstonia solanacearum (73). It is likely that the downregulation of Flp pilus genes is also responsible in part for the motility phenotypes observed in Fig.…”
Section: Global Pattern Of Qs-dependent Gene Expression In Bgpg1supporting
confidence: 61%
“…Flp pili are involved in surface attachment and in pathogenic interactions with eukaryotic hosts. The tad (tight adherence) macromolecular transport system represents an ancient subtype of the type II secretion system (T2SS) and is essential for pilus biogenesis (72,73). The BGPG1 genome encodes a single cluster of Flp pilus genes on chromosome 1.…”
Section: Global Pattern Of Qs-dependent Gene Expression In Bgpg1mentioning
confidence: 99%
“…Details about the characteristics of Tfpb in other systems, specifically, plant-associated bacteria, are only slowly emerging (19). The genome of the plant symbiont S. meliloti contains two gene clusters coding for Tfpb which belong to the Flp (fimbrial lowmolecular-weight protein) subfamily.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the importance of Tfp in plant-pathogen interactions is demonstrated in Xylella fastidiosa, where they help in the spread of the pathogen through grapevines (17). They also act as a virulence factor for Pseudomonas syringae in tobacco and Ralstonia solanacearum in potato plants (18,19). Despite the presence of Tfp genes in rhizobia, their role in bacterium-plant symbiosis is currently unknown.…”
mentioning
confidence: 99%
“…In addition, type IV pili (T4P) have also been shown to be involved in virulence of pathogenic bacteria, including P. aeruginosa, Neisseria meningitidis, and Ralstonia solanacearum (51)(52)(53). In this study, the PilZ proteins were found to regulate sliding motility, among which PXO_00049 acts as a positive regulator, whereas both PXO_02374 and PXO_02715 function as the negative ones.…”
Section: Fig 6 Subcellular Localization Of Pilz Domain Proteins In Pxo99mentioning
confidence: 81%